Towards a Better Understanding of Open Source Hardware Design Reuse in Company-Community Collaboration - Ezoji, Amer; Pinquié, Romain; Boujut, Jean-François (Advances on Mechanics, Design Engineering and Manufacturing III, 2021)
The open-source-software movement that emerged in the late 90s has recently extended to hardware. In this paper, we try to better understand how the reuse of design solutions facilitates company-community collaboration. On the one hand, based on existing research studies, we analyze three fundamental questions - 1) who wants to reuse a design? 2) Why do they want to reuse a design?, and 3) How do they reuse a design? - from a company perspective and a community perspective. On the other hand, we identified that companies and communities must create a common understanding of the design problems and solution and they could benefit in reusing design artifact to speed up the development time and improve the quality and transferability of the results. However, this research shows that companies and communities don’t use the same type of tools and methods to reuse design knowledge which may cause some problems for collaboration.